2017
DOI: 10.1093/nar/gkx738
|View full text |Cite
|
Sign up to set email alerts
|

Computational characterization of chromatin domain boundary-associated genomic elements

Abstract: Topologically associated domains (TADs) are 3D genomic structures with high internal interactions that play important roles in genome compaction and gene regulation. Their genomic locations and their association with CCCTC-binding factor (CTCF)-binding sites and transcription start sites (TSSs) were recently reported. However, the relationship between TADs and other genomic elements has not been systematically evaluated. This was addressed in the present study, with a focus on the enrichment of these genomic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 41 publications
3
44
0
Order By: Relevance
“…Many models and computational approaches have been developed to predict chromatin interactions and topological domain boundaries. These include an eclectic collection of computational methods including TADLactua [88], PCGS [89], nTDP [90] and BART [80]. TADLacuta utilised random forest and deep learning methods and integrated histone modifications, CTCF binding and transcription factor motifs predict TAD boundaries with an AUC ROC accuracy 0.867 [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many models and computational approaches have been developed to predict chromatin interactions and topological domain boundaries. These include an eclectic collection of computational methods including TADLactua [88], PCGS [89], nTDP [90] and BART [80]. TADLacuta utilised random forest and deep learning methods and integrated histone modifications, CTCF binding and transcription factor motifs predict TAD boundaries with an AUC ROC accuracy 0.867 [88].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why in our analysis HICRs contain elements with both active and inactive modifications indicating that these potential EPI regions may contain a mixture of active, inactive, poised and primed enhancer and promoter elements. Hong et al, [89] developed population greedy search algorithm (PGSA) to identify boundary enriched motifs and concluded that in addition to CTCF other TF such as ZNF143, ZNF274, YY1, SP1, ZNf274 and chromatin accessibility (DHS) as well as epigenetic modifications H3K36me3, gene associated features and protein complexes such as RNA PolII, TSSs were all enriched at TAD boundaries. Similarly Sefer and Kingsford developed a convex semi-nonparametric approach called nTDP based on Bernstein polynomials to explore the joint effects of histone markers on TAD formation [90].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, TFs with more constant roles such as NR2C2 (O'Geen et al, 2010) show very little difference between cell types. Interestingly, ZNF274 and SIX5, which were shown to relate to CTCF binding sites (Hong and Kim, 2017), also have low specificity similar to CTCF. Fig s5 lists the individual rewiring events with top values.…”
Section: Quantification Of Tf Regulation Rewiring Using Topic Weightsmentioning
confidence: 99%
“…preventing chromatin inter-domain interactions. They show not only enrichment in binding sites for DNA-binding proteins, such as CTCF, ZNF143, SMC, and YY1 but also specific histone epigenetic modifications, such as H3K36 trimethylation (H3K36me3), and Transcription Starting Sites (TSS) of housekeeping genes (Hong and Kim 2017).…”
Section: Introductionmentioning
confidence: 99%